Energetic Viability of a Dense Plasma Focus‑Based Fusion‑Fission Hybrid Reactor: Gas‑Cooled Fast Reactor Concept - García Gallardo, Jorge A. (New Energy Exploitation and Application, 2025)
The Fusion‑Fission Hybrid Reactor (FFHR) is a sort of reactor that generates energy through a subcritical set, using neutrons produced in a nuclear fusion device. The viability of such a reactor has already been studied by many authors. One of the most challenging problems to solve is that the energy generated by fission is usually insufficient to feed the fusion device, but this could be addressed by using a Dense Plasma Focus (DPF) as a neutron source in conjunction with the so‑called Multiplying Cascade (MC), which is a concentric arrangement of the fuel elements. The DPF is a very cheap and simple device that acts as a pulsed neutron source and seems to be promising in the future nuclear industry. The use of composite materials like cermets as fuel can improve energy efficiency by raising the operational temperature of the core. Also, a blanket of FLiBe, which is a molten salt, can provide the required amount of tritium by using the outgoing neutron flux. Because of the fast spectrum of this device, the use of gas as a coolant becomes convenient. In this way, the FFHR becomes a Gas‑cooled Fast Reactor (GFR), allowing it to combine high temperature and fast spectrum. It is possible to find a function of energy that indicates under what conditions the reactor can run. As the system includes fusion and fission in the same device, it inherits from both processes the concepts of criticality and break‑even at the same time.